Variable data structures and customized deep learning surrogates for computationally efficient and reliable characterization of buried objects - Yurt, Reyhan; Torpi, Hamid; Kizilay, Ahmet; Koziel, Slawomir; Mahouti, Peyman (NATURE PORTFOLIO, 2024)
In this study, in order to characterize the buried object via deep-learning-based surrogate modeling approach, 3-D full-wave electromagnetic simulations of a GPR model have been used. The task is to independently predict characteristic parameters of a buried object of diverse radii allocated at different positions (depth and lateral position) in various dispersive subsurface media. This study has analyzed variable data structures (raw B-scans, extracted features, consecutive A-scans) with respect to computational cost and accuracy of surrogates. The usage of raw B-scan data and the applications for processing steps on B-scan profiles in the context of object characterization incur high computational cost so it can be a challenging issue. The proposed surrogate model referred to as the deep regression network (DRN) is utilized for time frequency spectrogram (TFS) of consecutive A-scans. DRN is developed with the main aim being computationally efficient (about 13 times acceleration) compared to conventional network models using B-scan images (2D data). DRN with TFS is favorably benchmarked to the state-of-the-art regression techniques. The experimental results obtained for the proposed model and second-best model, CNN-1D show mean absolute and relative error rates of 3.6 mm, 11.8 mm and 4.7%, 11.6% respectively. For the sake of supplementary verification under realistic scenarios, it is also applied for scenarios involving noisy data. Furthermore, the proposed surrogate modeling approach is validated using measurement data, which is indicative of suitability of the approach to handle physical measurements as data sources.
Keywords: Artificial intelligence; Buried object characterization; Deep regression network; Ground penetrating radar (GPR); Surrogate modeling; Time frequency spectrogram; GROUND-PENETRATING RADAR; CLUTTER REMOVAL; GPR DATA; TIME; PROPAGATION; MACHINE; DESIGN; IMAGES; CLASSIFICATION; RECOGNITION; Science & Technology - Other Topics